KOMUNIKASI INTERPERSONAL ORANG TUA DAN ANAK DALAM MENGEMBANGKAN AKHLAK PADA ANAK REMAJA DI KANDANG RODA RT 02 KABUPATEN BOGOR - Kurniawan Nurul Ghani; Asep Guanawan, Noor Isna Alfaien (Jurnal Komunikasi, 2025)
There are many cases of violations committed by minors. According to the Indonesia Child Protection Commission (KPAI) during 2016-2020, there were a total of 24,974 cases of juvenile delinquency, 1,243 of which were social and child cases in emergency situations, 1,486 cases of health and drugs, 3,194 cases of education dominated by cases of bullying at school, 6,500 cases of children facing the law, and other cases. This study aims to understand interpersonal communication between parents and children in the process of moral development of adolescents. Therefore, the method to be used is qualitative research. Qualitative research is descriptive and tends to use analysis. The results obtained showed thatinterpersonal communication between parents and adolescents in the home environment plays an important role in developing adolescent morals. Even though the behavioral changes that occur are not significant, interpersonal communication still plays a role in the change. Direct interaction between parents and adolescents allows for faster and more effective feedback so that interpersonal communication can run smoothly. A relaxed and familiar communication style makes teenagers more comfortable talking to parents, but it must be with parental teaching. The process of interpersonal communication between parents and children in developing the morals of adolescents involves two-way interaction where children and parents are open to each other. Which then creates a positive environment and strengthens trust. Although obstacles are always present, patience and a deeper understanding are needed to overcome obstacles